A case report on incest relationship between brothers and sisters on birth labor from a judicial approach [Doǧum eylemi̇ndeki̇ erkek kız kardeş ensest olgusuna adli̇ yönden yaklaşım-Olgu sunumu] - (:unkn) unknown (Turkish Society of Obstetrics and Gynecology, 2012)
The incest case between brothers and sisters living in Eastern Anatolian Region was evaluated. In the labor, which was a total surprise for the incest victim female child herself, after examining the child, the specialist asked her if she was married or not. When he realized that the victim was maiden, he cleared the family out of the room and called the police. Until the police showed up, he didn't let the victim out and after the arrival of the police he delivered the 2200 gr. weighing baby from a normal spontaneous vaginal birth. After all these, the specialist turned the victim and the baby to the police. The police took the victim and the baby under protection. In our case the specialist who posted a notice, in the first stage has evaluated if the case was judicial or not. Then, because this was a judicial case, according to the 280th Article of TPC (Turkish Penal Code) he made the necessary notice to the police forces. By considering the 136th and 137th Articles of TPC, he didn't inform the families of the victim and prevented the child from a potential honor killing.
Keywords: Delivery; Forensic Case; Incest; Secrecy